Optimalisasi Pos Bantuan Hukum dalam Pemberian Hak Warga Negara pada Kasus Pidana di Pengadilan Negeri - Windi Riyani; Aziza Aziz Rahmaningsih; Firmansyah (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
The implementation of Legal Aid provided by Posbakum at the Metro District Court is one of the various ways to help underprivileged people access their legal rights. This research focuses on the formulation of strategies on evidence of protection of citizens' rights by providing access for the public through legal assistance facilitated by the Metro District Court through posbakum. This paper also identifies the important components that make this legal aid post a solution for justice-seeking communities. This research uses qualitative methods to gain a deep understanding of the needs of the underprivileged community in resolving their cases in the District Court. And the results underscore how important it is to address the challenges faced by communities in obtaining justice and legal certainty in their needs from the legal aid post that can be felt.